2004
DOI: 10.1345/aph.1d621
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Clinically Significant Gastrointestinal Toxicity Associated with Nonsteroidal Antiinflammatory Drugs

Abstract: COX-2 inhibitors and proton-pump inhibitors are effective and well-tolerated therapies to reduce clinically significant upper gastrointestinal adverse events associated with NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
(152 reference statements)
0
9
0
2
Order By: Relevance
“…As initially discussed by Wallace (173), there is ample evidence that selective inhibitors of COX-2 produce less gastric damage than standard NSAIDs when administered acutely to healthy animals. However, most patients taking standard NSAIDs do not develop clinically significant gastric injury, although a subset of patients is more susceptible to the gastric-damaging actions of these drugs (54). Moreover, the presence of both NOS isoforms in the vasculature raises the question of which is the predominant cause of the increased production of vasodilatory PGs that are critical to preserving renal blood flow during volume depletion and dehydration stress.…”
Section: Physiological Implications Of the Modulation Of The Cyclooxymentioning
confidence: 99%
“…As initially discussed by Wallace (173), there is ample evidence that selective inhibitors of COX-2 produce less gastric damage than standard NSAIDs when administered acutely to healthy animals. However, most patients taking standard NSAIDs do not develop clinically significant gastric injury, although a subset of patients is more susceptible to the gastric-damaging actions of these drugs (54). Moreover, the presence of both NOS isoforms in the vasculature raises the question of which is the predominant cause of the increased production of vasodilatory PGs that are critical to preserving renal blood flow during volume depletion and dehydration stress.…”
Section: Physiological Implications Of the Modulation Of The Cyclooxymentioning
confidence: 99%
“…Recent clinical trials have shown that the use of two of these inhibitors, celecoxib and rofecoxib, is associated with effective anti-inflammatory relief in osteoarthritis and rheumatoid arthritis as well as with a significantly lower incidence of ulcer complications [34][35][36].…”
Section: Reactive Oxygen Species and Gastric Ulcerationmentioning
confidence: 99%
“…Compared to NSAID plus PPI, co-therapy with misoprostol may be associated with a higher incidence of gastrointestinal symptoms (diarrhea, abdominal pain and flatulence), [14][15][16] while sucralfate, 17,18 and H 2 -receptor antagonists 17,[19][20][21][22][23] may be less efficacious. Although both a COX-2 selective inhibitor or a non-selective NSAID in conjunction with a PPI are considered effective strategies for reducing the risk of ulcer complications, 24,25 limited information is available regarding direct comparisons of risk-benefit and cost effectiveness of these two therapeutic op-tions. The decision about which protective strategy to choose remains controversial and requires consideration of the delicate balance between risks, benefits, and costs.…”
Section: Introductionmentioning
confidence: 93%